A Comparison of Neorealism, Liberalism, and Constructivism in Analysing Cyber War - Rika Isnarti (Andalas Journal of International Studies (AJIS), 2016)
Cyberwar can be considered as one of phenomena in International Relations. However, recently, there are not many literature about International Relations theory talking about cyber war or cyberspace generally. The phenomena of cyberspace is matter to International Relations as it involved sovereignty, state interactions and other elements in International Relations theory. On the other hand, cyber space blurs many concept in International Relations such as sovereignty is borderless in the realms of cyber space. Therefore, this articles analyses three perspectives in International Relations in analyzing cyber war. It explains what cyber war in context of International Relations, how three theories in International Relations with their elements analyses actors and interaction in cyber space. Finally, it found that Neorealism is the most adequate theory among other two theories in analyzing cyber war.